(untitled) (Transport systems and technologies, 2019)
The paper shows the study results of the braking efficiency of an electric train with a low coefficient of wheel adhesion to the rail (wheel sliding) in the speed range with the braking starting at 40–200 km/h. The studies were performed using mathematical and computer modeling. The results showed that the braking distance of the electric train at a speed of 200 km/h and continuous actuation of the wheel slide protection within 37.4 s (44% of the total braking time) and the wheel sliding on 50% of wheelsets is equal to 1933 m, which is less than the reference value of 1940 m. The diagrams and characteristics of the braking in the speed range of 40–200 km/h have been shown with the wheel slide protection in action.